Neoliberalism and criminal politics: An analysis on the management of the unwelcome within the brazilian reality - Monteiro Garcia, Renata; Vieira Fernandes Silva, Ana Rafaella; Wanderley Tannuss, Rebecka; Gomes de Sant’Ana e Silva Junior, Nelson (Journal Studies of Public Policy, 2022)
This paper aims to reflect upon Criminal Politics in regard to neoliberalism, as in Critical Criminology’s marxist-inspired norms, composing a brief analysis on the Brazilian reality. It is a theoretical literature review study, which weaves analysis on Brazil’s neoliberal agenda model and, subsequently, quests to comprehend by which means the Criminal Politics takes on as the centrepiece in this agenda, acknowledging the demand for social control through the disciplining of the labouring class and the penalisation of poverty as rebuttal to social exclusion and inequality.